PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL PADA SEKOLAH BERASRAMA DI BOJONEGORO - Roudlotun Ni’mah; Siti Labiba Kusna; Eshthih Fithriyana (Institut Keislaman Abdullah Faqih Gresik, 2018)
Abstract: This research is a multicasts study that discusses local wisdom-based character education. Taking the noble values of culture is now fading away eroded by increasingly complex civilizations. The problem of fading cultural values can be seen with the rise of acts of violence and crime that can only be done by adults but also children. This research was conducted in two Islamic boarding schools that applied local wisdom-based character education, namely the At-Tanwir Islamic Boarding School and the Ar-Rosyid Islamic Boarding School. Research and apply the effectiveness of the application of education based on local wisdom to the character of students. Based on the results of the analysis of interview data, observations and qualitative and quantitative research this study found that the two Islamic boarding schools have provided local wisdom-based character education optimally. The study also found that local wisdom-based character education is very optimal in boarding schools such as Islamic boarding schools.Keywords: character building, local wisdom